Multiple sample selection in the estimation of intergenerational occupational mobility - Cheti Nicoletti (University of Essex, Institute for Social and Economic Research (ISER), 2008)
The estimation of occupational mobility across generations can be biased because of different sample selection issues as, for example, selection into employment. Most empirical papers have either neglected sample selection issues or adopted Heckman-type correction methods. These methods are generally not adequate to estimate intergenerational mobility models. In this paper, we show how to use new methods to estimate linear and quantile intergenerational mobility equations taking account of multiple sample selection.
Keywords: 330